IMPLEMENTATION OF APPOINTMENT AND DISMISSAL OF OFFICERS IN DEPARTMENT OF POPULATION AND CIVIL REGISTRATION AT MUSI RAWAS UTARA REGENCY BASED ON THE MINISTER OF HOME AFFAIRS OF THE REPUBLIC OF INDONESIA REGULATION NUMBER 76 OF 2015 - Dwi Rahma Okta Wulandari; Amirizal Amirizal; Amancik Amancik (Bengkoelen Justice : Jurnal Ilmu Hukum, 2021)
This study was aimed to analyze the mechanism for the appointment and the dismissal of officers in the Department of Population and Civil Registration at Muratara Regency based on Permendagri Number 76 of 2015, and the legality of the appointment and the dismissal of officers in the Department of Population and Civil Registration carried out by the Regent of Muratara Regency.The type of this research was normative that supported by interviews, using a statutory approach and research material sources of primary and secondary data which were collected through literature and field studies.The results of this study indicate that the mechanism for the appointment and the dismissal of officers in the Department of Population and Civil Registration at Muratara Regency is based on Permendagri Number 76 of 2015. The appointment and the dismissal of the Head of Department of Population and Civil Registration as a Primary High Officer Position in regency are under the authority of the Minister of Home Affairs, not the Regent. The regent is only authorized to make proposals for appointment (and dismissal) through the Governor and includes proposals for three names of candidates for appointment,  then one of them be elected by the Minister, stipulated by a Ministerial Decree, and inaugurated. The appointment and the dismissal of officers in Disdukcapil carried out by the Regent of Muratara Regency is illegal, considering that the dismissal of the head of Disdukcapil Department (Kadisdukcapil) and his new appointment in 2016 was carried out by the Regent, not by the Minister. Besides, there are no reasons and considerations (including the proposal for the appointment of an official candidate) for the dismissal of the previous Kadisdukcapil as stipulated in Permendagri Number 76 of 2015.